Customer Relationship Management melalui Orientasi Pasar dan Inovasi Organisasi untuk Meningkatkan Kinerja Pemasaran Bisnis Online - Rithmaya, Chitra Laksmi; Kholid, Ikhwan; Tianto, Reza (Fakultas Ekonomi Universitas Samudra, 2023)
The study aims to examine the effect of customer relationship management on marketing performance mediated by market orientation and organizational innovation. The data was obtained through a questionnaire distributed to 50 MSME respondents in Surabaya. Determination of respondents using the quota sampling method. The variables analyzed are customer relationship management, market orientation, organizational innovation, and marketing performance. The results of the study state that partially, customer relationship management has a significant and positive effect on market orientation, marketing performance, and work innovation; and that market orientation and organizational innovation have a significant and positive effect on marketing performance. Another result obtained is that organizational innovation is proven to be able to mediate the effect of customer relationship management on marketing performance. Market orientation is also proven to be able to mediate customer relationship management on marketing performance.